Both Arthroscopically Assisted Suture Button and Hook Plate Are Effective in Treating Acute High-grade Acromioclavicular Joint Dislocation: A Systematic Review - Liang, Junbo; Han, Dawei; Ying, Xiaofang; Chen, Cong; Luo, Hua (Arthroscopy, 2025)
To conduct a systematic review of clinical studies comparing the clinical outcomes of arthroscopically assisted suture button (AASB) and hook plate (HP) in the treatment of acute high-grade acromioclavicular joint (ACJ) dislocation to determine which technique provides superior clinical benefits. Two independent researchers conducted literature searches on the basis of Preferred Reporting Items from Systematic Reviews and Meta-analyses guidelines. PubMed, EMBASE, and the Cochrane Library were searched for studies that compared AASB and HP in treating acute high-grade (grade Ⅲ and greater) ACJ dislocation. Inclusion criteria included clinical studies that compared AASB and HP for acute Rockwood type III or greater dislocations with evaluations of functional outcomes (Constant score [CS], pain score, American Shoulder and Elbow Surgeons score, Disabilities of the Arm, Shoulder and Hand). Studies were excluded if they were case reports, reviews, or had missing data, revision procedures, or had loss to follow-up >20%. The methodologic quality of the included studies was assessed on the basis of Newcastle-Ottawa scale. In this systematic review, 14 studies with 782 participants were included, all of which were classified as Level III-IV evidence. The analysis of 12 studies showed that the AASB group (81.9-95.31) had only slightly greater postoperative CS compared with the HP group (77.5-92.38), with 9 studies reporting significant improvements, whereas 3 studies found no significant difference compared with the HP group. For pain outcomes, 4 studies showed lower pain score in the AASB group, whereas the rest found no significant difference; the visual analog scale scores ranged from 0.3 to 3.61 in the AASB group and 0.5 to 4.9 in the HP group. Operation time was generally longer in the AASB group (AASB: 48.3-89.39 minutes; HP: 40.77-76.5 minutes). Complication rates were similar (AASB: 0%-50%; HP: 0%-36.36%), with only 1 study reporting a greater incidence in the AASB group. Minimal clinically important difference analysis from 3 studies showed clinically significant improvements in CS with AASB, but no significant difference between AASB and HP for pain outcomes. AASB shows comparable outcomes to HP for acute high-grade ACJ dislocations, with similar ranges in clinical scores and complication rates. Although AASB shows some advantages in functional outcomes, the differences between the 2 methods are minimal, suggesting that both approaches are effective and safe. Level IV, systematic review of Level Ⅲ-IV studies.